Bot Net of Things – A Survey (International Journal of Engineering and Computer Science, 2018)
Internet of things is talk of the town now a days but the potential threat IoT has over the cyber safety is less emphasized. The possibility for attackers with all systems interconnected with no or less security measures installed in them, makes them vulnerable to all kinds of security attacks. Botnet consists of collection of private computers interconnected together and affected by malicious software, which can be controlled as a group without the owner’s knowledge. BotNet is roBot and Network combination, the bot here is the compromised device. Denial of service, spyware, email spam, click fraud, bit coin etc., and are some of the well-known attacks by botnet. Botnet control itself has become a community, which focuses on prevention, control and repair services. This paper focuses on detailed survey of botnet and it’s regarding features.